Twofold carbon-carbon bond formation by intra- and intermolecular radical reactions of aryl diazonium salts - Jasch, Hannelore; Landais, Yannick; Heinrich, Markus (Chemistry - A European Journal, 2013)
Cascade reactions: A variety of novel cascade reactions can be performed when the known and well-studied radical 5- or 6-exo-cyclization of an aryl diazonium salt is conducted in the presence of alkenes and further optional scavengers (see scheme). Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: aryl radicals; carbon-carbon bond formation; cascade reactions; cyclization; radical reactions